Intra-Discrete Typing Unit TcV Genetic Variability of Trypanosoma cruzi in Chronic Chagas' Disease Bolivian Immigrant Patients in Barcelona, Spain - Oliveira, Maykon Tavares de; Sulleiro, Elena; Silva, Maria Cláudia da; Silgado, Aroa; de Lana, Marta; da Silva, João Santana; Molina, Israel; Marin-Neto, J. Antônio (Frontiers in Cardiovascular Medicine, 2021)
Background:Trypanosoma cruzi has a high rate of biological and genetic variability, and its population structure is divided into seven distinct genetic groups (TcI-TcVI and Tcbat). Due to immigration, Chagas disease (ChD), caused by T. cruzi, has become a serious global health problem including in Europe. Therefore, the aim of this study was to evaluate the existence of genetic variability within discrete typing unit (DTU) TcV of T. cruzi in Bolivian patients with chronic ChD residing in Barcelona, Spain. Methods: The DNA was extracted from the peripheral blood of 27 patients infected with T. cruzi DTU TcV and the fragments of the genetic material were amplificated through the low stringency single primer-polymerase chain reaction (LSSP-PCR). The data generated after amplification were submitted to bioinformatics analysis. Results: Of the 27 patients evaluated in the study, 8/27 (29.6%) were male and 19/27 (70.4%) female, 17/27 (62.9%) were previously classified with the indeterminate clinical form of Chagas disease and 10/27 (37.1%) with Chagas cardiomyopathy. The LSSP-PCR detected 432 band fragments from 80 to 1,500 bp. The unweighted pair-group method analysis and principal coordinated analysis data demonstrated the existence of three distinct genetic groups with moderate-high rates of intraspecific genetic variability/diversity that had shared parasite's alleles in patients with the indeterminate and cardiomyopathy forms of ChD. Conclusions: This study demonstrated the existence of a moderate to high rate of intra-DTU TcV variability in T. cruzi. Certain alleles of the parasite were associated with the absence of clinical manifestations in patients harboring the indeterminate form of ChD. These results support the need to search for increasingly specific targets in the genome of T. cruzi to be correlated with its main biological properties and clinical features in patients with chronic ChD.